An Ordinance Relating to Concealed Weapons, §§ 1-5, in City of Portland Auditor's Fifty-First Annual Report of the Receipts and Expenditures of the City of Portland for the Financial Year of 1909 152-53 (1910). - (:unkn) unknown (General Publisher, 1909)
No person shall, within the corporate limits of the City of Portland, in a threatening manner display any firearm, slung shot, knuckles, bowie knife, dirk, stiletto, or other dangerous or deadly weapon. And no person shall, within the corporate limits of the City of Portland, wear under his clothes or concealed about his person any such fire arm, slung shot, knuckles, bowie knife, dirk, stiletto, or other dangerous or deadly weapon, unless first licensed so to do in the manner following:
--
Keywords: BRANDISHING; CARRY - CONCEALED